2003
DOI: 10.1210/jc.2002-021787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone Replacement on Parathyroid Hormone Sensitivity and Bone Mineral Metabolism

Abstract: Adult GH deficiency (AGHD) is associated with reduced bone mineral density, and decreased end-organ sensitivity to the effects of PTH has been suggested as a possible underlying mechanism. We investigated the effects of GH replacement (GHR) on PTH circulating activity and its association with phosphocalcium metabolism and bone turnover in 16 (8 men and 8 women) AGHD patients. Half-hourly blood and 3 hourly urine sampling was performed on each patient over a 24-h period before GHR and then after 1, 3, 6, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 49 publications
5
67
0
2
Order By: Relevance
“…These findings were associated with low bone turnover and changes in phosphocalcium metabolism in untreated AGHD patients, suggesting decreased end-organ sensitivity to the effects of PTH (2). In a more recent study (4), we demonstrated that growth hormone replacement (GHR) significantly decreases PTH concentration with changes in PTH secretory pattern and a significant increase in NcAMP. In addition, we observed a significant increase in bone turnover and changes in phosphocalcium metabolism, suggesting an increase in end-organ sensitivity to PTH.…”
mentioning
confidence: 76%
“…These findings were associated with low bone turnover and changes in phosphocalcium metabolism in untreated AGHD patients, suggesting decreased end-organ sensitivity to the effects of PTH (2). In a more recent study (4), we demonstrated that growth hormone replacement (GHR) significantly decreases PTH concentration with changes in PTH secretory pattern and a significant increase in NcAMP. In addition, we observed a significant increase in bone turnover and changes in phosphocalcium metabolism, suggesting an increase in end-organ sensitivity to PTH.…”
mentioning
confidence: 76%
“…3,4 ‱Circadian rhythm parameters evaluated were: 1) midline estimate statistic of rhythm (MESOR), rhythm-adjusted mean; 2) amplitude and 3) acrophase.…”
Section: Discussionmentioning
confidence: 99%
“…over that of 24,25(OH)2D3 with a moderate increase in intestinal Ca absorption in dogs (27). In a study in GHD humans, GH administration at bedtime caused a nocturnal increase in PTH production followed by a decrease in PTH during daytime as compared with untreated GHD adults (28). It could be hypothesized that such a 24-h PTH pattern during GH therapy could be beneficial for bone density.…”
Section: Discussionmentioning
confidence: 99%